REFLECTIVE TEACHING TOWARD EFL TEACHERS’ PROFESSIONAL AUTONOMY: REVISITING ITS DEVELOPMENT IN INDONESIA - Lubis, Arif Husein (International Journal of Education, 2018)
It has been approximately 25 years that reflective teaching in EFL context, particularly in Asia is being encouraged and reviewed. The notable goal emphasizes the teachers’ role as critical lifelong learners in or outside the classroom to bring about continuous mutual development between them and the surroundings. Although myriad research-based studies have paid attention to the developmental praxis of reflective teaching, scant published articles highlight the progress of its empowerment process and quality in Indonesia. Thus, this paper will address some points related to how this realm is being concerned and developed reflecting from the preceding and contemporary discussion and its milestone in Indonesia within Asia scope. Furthermore, the envision of future direction is prompted from current portrait, existing challenges, and expectations concerning the theoretical foundation, means and models, ICT integration, and character education toward 21st-century English teachers’ professional autonomy.